Investigating checkpoint inhibitor-induced gastrointestinal disease: comparisons with idiopathic ulcerative colitis and health - Gupta, T (2022)
In the last decade, immunotherapy with anti-PD1 and anti-CTLA4 drugs has revolutionized the treatment of metastatic cancer. A significant proportion of patients given these checkpoint inhibitors develop off-target inflammation in the colon (checkpoint inhibitor-induced colitis, CC). Ulcerative colitis (UC) is a well-characterized multisystem disorder, propagated by a combination of barrier defects, immune dysfunction and a disordered microbiome, all on a background of genetic susceptibility. The underlying mechanisms of both checkpoint inhibitor-induced colitis and ulcerative colitis remain poorly understood, with a significant proportion of patients failing therapy. Using clinical data, next-generation single-cell RNA sequencing, unbiased spatial transcriptomics and organoid model systems, we elucidate clinically relevant patterns of cellular behaviour across blood, epithelium, stroma and immune populations. We describe and characterize novel disease-specific cell populations and cellular interactions in tissue ‘microdomains’ with functional relevance. Our work has implications for therapeusis as well as puts forward a new approach for identifying drug-bound cells in vivo.